Comparando a interação social de crianças autistas: as contribuições do programa TEACCH e do Currículo Funcional Natural. - Giardinetto, Andréa Rizzo dos Santos Boettger (2005)
The work with autistic children is surrounded by controversy. Thus several interpretations about its characterization and possible intervention models have been presented. In addition, methodologies and measures used in studies on intervention programs differ greatly, making the comparison among these programs difficult. However, positive results show that early intensive education involving both parents and teaching of essential skills is able to promote significant and positive changes in development areas of children with autism, such as the areas of communicative and social interaction skills. In Brazil, institutions have adopted different intervention programs for treatment and education of children with autism, especially TEACCH and Natural Functional Curriculum (at lesser proportions). Since these two programs have been widely used in Brazil, and considering that there are few studies comparing different approaches, among which there are some with methodological problems, the objectives of this research were to compare the social interaction of children with autism by analyzing their communicative behaviors and analyze the classroom ecology. Six children with autism, matched for age, sex, length and frequency of treatment, communication, and educational level of their mothers, participated in this research, which was carried out in two institutions from two different cities of the interior of São Paulo State. Three of these children were attended by TEACCH, while the others were attended by Natural Functional Curriculum. Their communicative behaviors were observed during the classroom activities by using the communicative profile protocol, and the classroom ecology was analyzed through a checklist of the variables which compose the intervention programs. Sixty-six films, each with a length of 30 minutes (1980 minutes in total), were recorded in a period of nine months. The results of the current study indicated that the children attended by the Natural Functional Curriculum program showed more communicative behaviors of social interaction and performed more activities under teacher s instructions than those attended by TEACCH. However, further research is necessary to better describe and compare intervention programs for children with autism in Brazil.